Meso - Rex shunt using the inferior mesenteric vein in a paediatric patient - Yaying Eileen Xu; Craig A. McBride; Peter Hodgkinson (Elsevier, 2020)
Extrahepatic portal vein obstruction primarily results from congenital vascular malformations or acquired portal venous thrombosis. Portal hypertension can lead to various complications such as recurrent upper gastrointestinal hemorrhage secondary to varices, ascites, hypersplenism, or encephalopathy. Meso-rex shunt is a curative surgical procedure that uses autologous vein graft as a bypass to redirect blood from the superior mesenteric vein (SMV) to the patent intrahepatic left portal vein in patients. The most common vein graft used is internal jugular vein (IJV) harvested from the patient's neck. Meso-Rex shunt using the inferior mesenteric vein (IMV) has been rarely described in the literature. It avoids neck dissection and its associated complications. It also reduces the number of anastomoses down to one. We report a 14-year-old girl who underwent a successful meso-Rex shunt using the IMV and summarize the literature.